Accountability studies in religious Non-Profit Organizations: Possible contextual and application gaps - Zubaidah Mohd Ali; Rozaidy Mahadi (Macrothink Institute, 2021)
Having substantial accountability standards and practices is a vital practice to ensure the survival of Religious-Based Non-Profit Organisations (RNPOs). This is because the RNPOs are not only representing the religion’s ideals but at the same time, there are also responsible in disseminating ethical massage and good values in the community. Since the RNPOs played a significant role in society, many studies have highlighted the need to explore more accountability issues involving RNPOs. Hence, this study aims to provide a taxonomical review of literature that examined RNPOs’ accountability practices and subsequently, suggesting plausible contextual and application gaps for future research. In so doing, this study utilised van Helden and Nortcott’s (2010) and Rozaidy, Siti Nabiha, Rasid, and Raman (2017) taxonomical methods in categorising accountability studies in RNPOs. As a result, four main themes have been identified from 60 selected high-impact journal articles. The four themes are 1) examining the outcomes of corporate integrity and accountability practices; 2) evaluating the RNPOs’ internal control practices; 3) identifying financial reporting disclosures practices among RNPOs; and 4) exploring the influence of leadership skills on RNPOs’ accountability practices.